Relationship Between School Climate and Teacher Job Satisfaction: A Meta-Analytic Study - Ningtyas, Lisa Dwi (RSF Conference Series: Business, Management and Social Sciences, 2024)
It is said that a professional teacher is a teacher who performs well. One indicator of a teacher's good performance is that it can be seen from the high level of job satisfaction of the teacher. It is expected that teachers who have high job satisfaction can increase their professionalism in their work. Several previous studies said a relationship exists between school climate and teacher job satisfaction. Unlike previous research, this study aims to determine the strength of the relationship or the magnitude of the difference between school climate and job satisfaction through a meta-analysis method with ten highly reputable articles. The results show that school climate positively correlates with teacher job satisfaction. The advice is to obtain information about administration and management in developing a school climate. This is because the school climate can facilitate teacher job satisfaction by increasing teacher professionalism in performance to produce quality students following the goals of Indonesian education stated in the curriculum regarding educational goals.